An integrative approach-using field and laboratory data to characterize shell utilization and selection pattern by the hermit crab Pagurus criniticornis (Paguridae) from Anchieta Island, Brazil - Fernando L. Mantelatto; Fabíola C. R. Faria; Renata Biagi; Andrea L. Meireles (Nauplius)
Abstract The aim of this study was to characterize the pattern of gastropod shell occupation in the field and selection of shell size and type under laboratory conditions by the hermit crab Pagurus criniticornis (Dana, 1852), inhabiting the infralittoral area of Anchieta Island, São Paulo, Brazil. Hermit crabs were obtained monthly during 1999 by SCUBA diving. For experiments under laboratory conditions, samplings were performed in 2002. The hermit crabs occupied 16 species of gastropods shells. Cerithium atratum (Born, 1778) was the most occupied shell (89.31%), followed by Morula nodulosa (4.73%) (Adams, 1845). No difference was observed in the pattern of occupation between males and females. The equations that best demonstrated the relationship between hermit crabs and their shells were those that involved Shell Wet Weight (SWW) and Shell Internal Volume (SIV). The laboratory experiments were in accordance to the pattern of occupation observed in the field; the mean value of SAI (Shell Adequacy Index) recorded to the population studied was 1.13 with a trend to increase this value in the last size classes. The results obtained corroborate with the hypothesis of the occupation process of shells governed not only by availability of shells, but also by its architecture. In addition, the shell stock in the area is one another important condition related to the exhibited pattern of shell occupation by P. criniticornis, and allows the stable coexistence among the island assemblage. The pattern of occupation observed promotes a high reproductive profile for the population studied, maximizing the populational growth.